Inventory Model for Deteriorating Items with Life Time - Kumar, Rajender; Pruthi, Manju; Taneja, Gulshan (International Journal of Engineering and Technology, 2018)
In this paper, an inventory model of deteriorating items with life time has been discussed. The demand rate has been taken of cubic function of time which starts from zero in the beginning and ends to zero at the completion of the cycle. The deterioration rate is assumed to be of power pattern , i.e. . Shortages are allowed and fully backlogged.Â